Osthole improves glucose and lipid metabolism via modulation of PPARα/γ-mediated target gene expression in liver, adipose tissue, and skeletal muscle in fatty liver rats. (3rd May 2016) - Qi, Zhi-Gang; Zhao, Xi; Zhong, Wen; Xie, Mei-Lin
Abstract: Context : Osthole may be a dual agonist of peroxisome proliferator-activated receptors (PPAR) α/γ and ameliorate the insulin resistance (IR), but its mechanisms are not yet understood completely. Objective : We investigated the effects of osthole on PPARα/γ-mediated target genes involved in glucose and lipid metabolism in liver, adipose tissue, and skeletal muscle in fatty liver and IR rats. Materials and methods : The rat model was established by orally feeding high-fat and high-sucrose emulsion for 9 weeks. The experimental rats were treated with osthole 5–10 mg/kg by gavage after feeding the emulsion for 6 weeks, and were sacrificed 4 weeks after administration. Results : After treatment with osthole 5–10 mg/kg for 4 weeks, the lipid levels in serum and liver were decreased by 37.9–67.2% and 31.4–38.5% for triglyceride, 33.1–47.5% and 28.5–31.2% for free fatty acid, respectively, the fasting blood glucose, fasting serum insulin, and homeostasis model assessment of IR were also decreased by 17.2–22.7%, 25.9–26.7%, and 37.5–42.8%, respectively. Osthole treatment might simultaneously decrease the sterol regulatory element binding protein-1c, diacylglycerol acyltransferase, and fatty acid synthase mRNA expressions in liver and adipose tissue, and increase the carnitine palmitoyltransferase-1A mRNA expression in liver and glucose transporter-4 mRNA expression in skeletal muscle, especially in the osthole 10 mg/kg group ( p  < 0.01). Discussion and conclusion : Osthole can improve glucose and lipid metabolism in fatty liver and IR rats, and its mechanisms may be associated with synergic modulation of PPARα/γ-mediated target genes involved in glucose and lipid metabolism in liver, adipose tissue, and skeletal muscle.